Short-term chamber exposure to low doses of two kinds of wood smoke does not induce systemic inflammation, coagulation or oxidative stress in healthy humans. (26th June 2013) - Stockfelt, Leo; Sallsten, Gerd; Almerud, Pernilla; Basu, Samar; Barregard, Lars
Abstract: Introduction : Air pollution increases the risk of cardiovascular diseases. A proposed mechanism is that local airway inflammation leads to systemic inflammation, affecting coagulation and the long-term risk of atherosclerosis. One major source of air pollution is wood burning. Here we investigate whether exposure to two kinds of wood smoke, previously shown to cause airway effects, affects biomarkers of systemic inflammation, coagulation and lipid peroxidation. Methods : Thirteen healthy adults were exposed to filtered air followed by two sessions of wood smoke for three hours, one week apart. One session used smoke from the start-up phase of the wood-burning cycle, and the other smoke from the burn-out phase. Mean particle mass concentrations were 295 µg/m 3 and 146 µg/m 3, and number concentrations were 140 000/cm 3 and 100 000/cm 3, respectively. Biomarkers were analyzed in samples of blood and urine taken before and several times after exposure. Results after wood smoke exposure were adjusted for exposure to filtered air. Results : Markers of systemic inflammation and soluble adhesion molecules did not increase after wood smoke exposure. Effects on markers of coagulation were ambiguous, with minor decreases in fibrinogen and platelet counts and mixed results concerning the coagulation factors VII and VIII. Urinary F2 -isoprostane, a consistent marker of in vivo lipid peroxidation, unexpectedly decreased after wood smoke exposure. Conclusions : The effects on biomarkers of inflammation, coagulation and lipid peroxidation do not indicate an increased risk of cardiovascular diseases in healthy adults by short-term exposure to wood smoke at these moderate doses, previously shown to cause airway effects.